Non-bank finance for firms. The role of private equity funds in north-western Italy - Daniele Coin; Valerio Vacca (European Regional Science Association (ERSA), 2014)
Using fund-, firm- and bank-level data we investigate the investments of private equity (PE) funds in the north-western regions of Italy. Both the private equity fund managers and the PE investments are heavily concentrated in this most developed area of the country. The average size of the portfolios is small by international standards and their concentration by firm has been growing after the 2008 crisis. The average duration of investments is rather short (about 3.4 years) and just 10 per cent of them target firms which are both young and innovative. PE investments are more significant for north-western firms than for those in the rest of the country, relative to traditional bank credit. We find that being participated by a PE fund increases the amount of credit obtained by the target firm and (weakly) reduces its cost. However, this effect is exclusively related to the entry of the fund in the firm's capital, as it fades away as soon as the fund exits from the capital, thus suggesting a weak signalling role of PE towards banks.
Keywords: G23; G24; G28; G32; 330; private equity; fund portfolio